Behavioral Paradigms to Probe Individual Mouse Differences in Value-Based Decision Making - Alabi, Opeyemi O.; Fortunato, Michael P.; Fuccillo, Marc V. (Frontiers in Neuroscience, 2019)
Value-based decision making relies on distributed neural systems that weigh the benefits of actions against the cost required to obtain a given outcome. Perturbations of these systems are thought to underlie abnormalities in action selection seen across many neuropsychiatric disorders. Genetic tools in mice provide a promising opportunity to explore the cellular components of these systems and their molecular foundations. However, few tasks have been designed that robustly characterize how mice weigh differential reward benefits and cost in their selection of actions. Here we present a forced-choice, two-alternative task in which each option is associated with a specific reward outcome and unique operant contingency. We developed global and individual trial measures to assess the choice patterns and behavioral flexibility of mice in response to differing “choice benefits” (modeled as varying reward magnitude ratios) and different modalities of “choice cost” (modeled as either increasing repetitive motor output to obtain reward or increased delay to reward delivery). We demonstrate that 1) mouse choice is highly sensitive to the relative benefit of outcomes; 2) choice costs are heavily discounted in environments with large discrepancies in relative reward; 3) divergent cost modalities are differentially integrated into action selection; 4) individual mouse sensitivity to reward benefit is correlated with sensitivity to reward costs. These paradigms reveal stable individual animal differences in value-based action selection, thereby providing a foundation for interrogating the neural circuit and molecular pathophysiology of goal-directed dysfunction.